AS CERTIFICAÇÕES LEED E AQUA-HQE EM EDIFÍCIOS COMERCIAIS NO BRASIL E A AGREGAÇÃO DE VALOR - Lacerda, Cristiane; Carsalade, Flávio; Assis, Eleonora (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This article presents the research on the perception of value added in the construction, commercialization and operation phases of commercial buildings in Brazil, which have achieved LEED (Leadership in Energy and Environmental Design) and AQUA-HQE (High Environmental Quality or Haute Qualité Environnmentale) certification. The selected methodology was the elaboration and application of a questionnaire with 94 questions to the professionals at the construction companies or investors who carried out the entire certification process. The issues were aimed at covering the factors of value generation in three different stages of the commercial building's life cycle: in the construction phase, in the commercialization phase and in the operation and maintenance phase. The research resulted in the following conclusions: (a) aggregation of value in buildings does not necessarily require the achievement of a constructive sustainability certification. However, the certification can contribute to the generation of value; (b) the use of sustainable production methods required in certifications process contributes to the reduction of losses and reuse of materials and, consequently, generates economic benefits; (c) constructions with constructive sustainability certification presents competitive differentials and, therefore, generate economic advantages, and (d) constructions that have obtained constructive sustainability certification have lower costs of water and energy.